2010
DOI: 10.1021/jp910038j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Crossover and Breakdown of the Stokes−Einstein Relation in Confined Water and in Methanol-Diluted Bulk Water

Abstract: Using nuclear magnetic resonance and quasi-elastic neutron scattering spectroscopic techniques, we obtain experimental evidence of a well-defined dynamic crossover temperature T(L) in supercooled water. We consider three different geometrical environments: (i) water confined in a nanotube (quasi-one-dimensional water), (ii) water in the first hydration layer of the lysozyme protein (quasi-two-dimensional water), and (iii) water in a mixture with methanol at a methanol molar fraction of x = 0.22 (quasi-three-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
84
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 90 publications
(203 reference statements)
6
84
1
Order By: Relevance
“…These findings on confined water are subject to the concern that water behavior may be affected by the silica pore surfaces or the confinement constraints may affect its dynamic behavior, resulting in a physical situation very different from that of bulk water. The results on nanopore-confined water, however, have been confirmed by a number of different techniques (10,12,16) that also show the crossover at ∼225 K and thus are consistent with the possibility that the tetrahedral HB structure recovers at temperatures pertinent to studies of the hypothesized liquid-liquid transition (17).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…These findings on confined water are subject to the concern that water behavior may be affected by the silica pore surfaces or the confinement constraints may affect its dynamic behavior, resulting in a physical situation very different from that of bulk water. The results on nanopore-confined water, however, have been confirmed by a number of different techniques (10,12,16) that also show the crossover at ∼225 K and thus are consistent with the possibility that the tetrahedral HB structure recovers at temperatures pertinent to studies of the hypothesized liquid-liquid transition (17).…”
supporting
confidence: 66%
“…These findings on confined water are subject to the concern that water behavior may be affected by the silica pore surfaces or the confinement constraints may affect its dynamic behavior, resulting in a physical situation very different from that of bulk water. The results on nanopore-confined water, however, have been confirmed by a number of different techniques (10,12,16) that also show the crossover at ∼225 K and thus are consistent with the possibility that the tetrahedral HB structure recovers at temperatures pertinent to studies of the hypothesized liquid-liquid transition (17).To test the connection between water anomalies and water's HB network, we consider thermodynamic results on confined water and bulk water sound propagation data. In specific, we consider the velocity dispersion (18)(19)(20) asking to what extent is sound velocity in water v a function of the probe wave vector ðQÞ and the frequency (ω).…”
mentioning
confidence: 62%
“…15 The transition temperatures are rather higher than other estimates that have been used to support arguments for dynamic heterogeneities in supercooled water. [16][17][18][19][20] Chen et al 16 reported a fragile-to-strong crossover temperature of 225 K for light water based on NMR selfdiffusion measurements on confined samples a few nanometers in cross-section and on QENS spectra. The StokesEinstein relation was written in the form D Ϸ − , where is a translational relaxation time derived from the QENS experiments.…”
mentioning
confidence: 99%
“…1͒ shows a transition closer to 240 K. A later paper 18 from the same group, apparently based on a reworking of the same data, gives a higher crossover temperature of 290 K and exponents of 1 and 0.6. Still more recent work 20 reverts to the lower temperature, with exponents dependent on the degree of confinement. The capillary work was regarded as "quasi-onedimensional," experiments on protein surface water as "quasi-two-dimensional," and water in methanol solution as "quasi-three-dimensional."…”
mentioning
confidence: 99%
See 1 more Smart Citation